Usihanje podjetništva v Sloveniji: GEM Slovenija 2011 - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja (University of Maribor Press, 2012)
Declining Entrepreneurship in Slovenia : GEM Slovenia 2011. The GEM research programme was created to enable a harmonized study of different forms of entrepreneurship in vastly different countries – from the most developed to those where the majority of the population still lives below the poverty line. Entrepreneurship is always important, as it ensures and enables development, though its importance and influence are adjusted according to individual development stages of the economy and the enterprise. GEM provides a good understanding of societal values regarding entrepreneurship and individual entrepreneurship characteristics of individuals, such as their perception about business opportunities, the perception of their own capabilities to act entrepreneurially, their fear of failure, and their entrepreneurship intentions. The current study reveals the decline in early-stage entrepreneurship activity of the adult population and less entrepreneurship dynamism. Such a decline is combined with the consequences of the international economic and financial crisis. Special attention is also devoted to the study of entrepreneurial employee activity and its correlation with early-stage entrepreneurship activity at various developmental stages of economies.